Large scale energy storage using multistage osmotic processes: approaching high efficiency and energy density. Issue 3 (7th March 2017) - Bharadwaj, Devesh; Struchtrup, Henning
Abstract : A large-scale energy storage system using multistage osmotic processes is analysed, wherein, the process designed shows promising round trip efficiency and energy density, relative to single stage processes. Abstract : With the increase in ocean levels due to global warming, there is a desperate need for clean and renewable energy at this time, more than ever before. Although the economic front of technologies, such as wind and solar power, has shown improvement, the fact remains that these energy sources are intermittently available in nature. This calls for a reliable energy storage technology that can bridge the gap between the supply and demand of electricity, leading us to a world driven by clean and renewable energy. Here, we propose a process for storing electrical energy using engineered osmosis. To store electrical energy, a salty solution is separated into brine and fresh water streams using modified reverse osmosis. When there is a demand for electricity, the chemical potential is converted back into electrical work by mixing the solutions using a modified version of pressure retarded osmosis. With modelling and simulations, we demonstrate that the proposed process can achieve round trip efficiencies of 50–60% and energy densities equivalent to that of a 500 m high pumped-hydro plant. The results demonstrate a promising process to store electrical energy, which, unlike pumped-hydro, is unconstrained by geography.